Design of a High Step-Up DC-DC Converter with Voltage Doubler and Tripler Circuits for Photovoltaic Systems - Muhammad Yaseen; Ajmal Farooq; Muhammad Zeeshan Malik; Muhammad Usman; Ghulam Hafeez; Muhammad Ali (International Journal of Photoenergy)
In this paper, a high step-up DC-DC interleaved boost converter is proposed for renewable sources with low voltages such as photovoltaic module and fuel cell. The proposed converter uses interleaving method with an additional voltage doubler and tripler circuit. In the proposed converter, the inductor at all phases is operated to gain high voltage through voltage doubler and tripler circuit capacitors with suitable duty cycle. The proposed topology operates in six switching states in one period. The steady-state analysis and operating principle are examined comprehensively which shows numerous improvements over the traditional boost converter. These improvements are high-voltage gain and low-voltage stress across switches. The proposed DC-DC interleaved boost converter has a gain/conversion ratio four times that of the conventional interleaved boost converter and four times less-voltage stress across the main switches. Simulation has been done in Matlab Simulink on a 70% duty cycle, and results are compared with conventional interleaved boost converter. For an input voltage of 15 volts, the proposed converter is able to generate an output voltage of 200 volts at 70% duty cycle with a voltage stress of 50 volts across main switches, whereas traditional interleaved boost converter generates 200 volts from same input voltage at 92.5% duty cycle with voltage stress of 200 volts across switches. From simulation results, it is clear that the proposed converter has better performance as compared to conventional interleaved boost converter for same design parameters.